Chemical and sensory evaluation of Merlot wines fermented by mixed cultures of Lachancea thermotolerans and Saccharomyces cerevisiae - Gallo, Adelaide (2022)
Mestrado em Engenharia de Viticultura e Enologia (Double Degree) / Instituto Superior de Agronomia. Universidade de Lisboa / Faculdade de Ciências. Universidade do Porto